Definition and classification of administrative offenses against the state border security - Ksenziuk, Andrii (Migration & Law, 2023)
The article is aimed at addressing the issue of defining the definition of administrative offenses (delict) against the State border security, and the system and classification of these offenses (delict) in Ukraine. The author proposes to consider this definition as a socially harmful (dangerous), guilty and unlawful act of a person which encroaches upon the balanced state of protection of the State sovereignty and territorial integrity, as well as upon the interests of a person, society and the State in the border area protected by the legislation on the State border, and for which administrative liability is provided for by law. It is established that the classification of administrative offenses (delict) against the border security of the State is of significant theoretical and applied importance. First of all, a proper classification of delicts creates a positive basis for establishing the most significant features among illegal and anti-State acts, for their proper delimitation and for applying fair administrative punishment for the offense to the perpetrators. In addition, the appropriate classification helps the competent authorities to properly qualify administrative offenses (delict) and choose appropriate administrative measures. Also, the classification makes it possible to determine the causes and conditions of the relevant administrative offense (delict) against the border security of the State, which allows for adequate preventive (preventive) measures to be taken.
Keywords: Administrative offenses; Delict; Signs of offenses; Border security